2021
DOI: 10.3168/jdsc.2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Apparent prevalence of Mycoplasma wenyonii, Candidatus Mycoplasma haemobos, and bovine leukemia virus in Wisconsin and Michigan dairy cattle herds

Abstract: Mycoplasma wenyonii and a related organism, Candidatus Mycoplasma haemobos, have been detected in both ill and apparently healthy cattle, but little is known about their prevalence in US dairy cattle. Blood samples were collected from 1,930 dairy cows on 64 Wisconsin farms and 591 dairy cows in 18 Michigan dairy farms. Samples were tested for Mycoplasma wenyonii and Candidatus Mycoplasma haemobos using whole-blood PCR, and were tested for serum antibodies to bovine leukemia virus using ELISA. This is the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, it is likely that the Mycoplasma circulated for some time in another, unknown reservoir host, diverged, and then contaminated the herd at several time points with different strains or alternatively was maintained in the herd for an extended period of time. Moreover, the mode of transmission is not known, but it has been suggested that insects that can transfer blood may play a role in the spread of M. wenyonii [26,27]. To the authors' knowledge, M. wenyonii DNA has only been detected once in a tick in Europe and that was in an I. ricinus tick collected from an infected animal [28].…”
Section: Prevalence Of Infectious Agents In Cattlementioning
confidence: 84%
See 1 more Smart Citation
“…Thus, it is likely that the Mycoplasma circulated for some time in another, unknown reservoir host, diverged, and then contaminated the herd at several time points with different strains or alternatively was maintained in the herd for an extended period of time. Moreover, the mode of transmission is not known, but it has been suggested that insects that can transfer blood may play a role in the spread of M. wenyonii [26,27]. To the authors' knowledge, M. wenyonii DNA has only been detected once in a tick in Europe and that was in an I. ricinus tick collected from an infected animal [28].…”
Section: Prevalence Of Infectious Agents In Cattlementioning
confidence: 84%
“…M. wenyonii is a haemoplasma that infects erythrocytes in cattle. This and another haemoplasma, M. haemobos, have been implicated in severe diseases in both Europe and the USA [26,27,29,30]. However, their clinical importance has been questioned because both haemoplasmas have been detected in sick as well as healthy cattle [31,32].…”
Section: Prevalence Of Infectious Agents In Cattlementioning
confidence: 99%
“…Elsewhere, higher prevalence than the results from this study were also reported. For example, the prevalence of 32.2% in Cuba [16], 28.6% in the Philippines [36], 64.2% in Brazil [19] and >90% in Japan and USA [17,18]. The variations in prevalence may be due to differences in laboratory procedures, climatic conditions, study population characteristics and sampling methods.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, infections with Mycoplasma wenyonii were reported [ 29 ]. Coinfection with both Mycoplasma species have been reported in different places [ 30 , 31 ]. Interestingly, using DNA sequence analysis of unmapped reads, we could also identify one animal that was detected with DNA of both Mycoplasma species.…”
Section: Discussionmentioning
confidence: 99%